2007
DOI: 10.1136/bmj.39203.430984.ad
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in classification of repeat sudden unexpected infant deaths in Care of the Next Infant programme

Abstract: It is misleading to classify every unexplained infant death as natural if no unnatural cause has been established, argue C J Bacon and E N Hey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Previous research by CONI12 showed most repeat deaths are due to natural causes, but some may be unnatural, raising concerns for professionals managing such families. However, there is no consensus on which proportion of repeat deaths may be unnatural,13 14 and much of the increased recurrence risk relates to parental smoking, maternal age and social deprivation 15. Since this last research the standard of UK SUDI investigation has improved considerably,16 enabling a cause of death to be determined in more cases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by CONI12 showed most repeat deaths are due to natural causes, but some may be unnatural, raising concerns for professionals managing such families. However, there is no consensus on which proportion of repeat deaths may be unnatural,13 14 and much of the increased recurrence risk relates to parental smoking, maternal age and social deprivation 15. Since this last research the standard of UK SUDI investigation has improved considerably,16 enabling a cause of death to be determined in more cases.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that 80-90% of second SIDS cases were natural (28). This paper has not gone without challenge, including by Dr. V. Dimaio, and review of Carpenter's data by other authors has suggested a higher rate of unnatural deaths (2931) than recorded by Carpenter et al Bacon and colleagues, in a review of papers on repeat SIDS, commented that the studies upon which risk of a second death was derived were flawed and may have overestimated the risk (31). They stated that by 2005, the risk of a first baby dying of SIDS in the UK was one in 3300 and of a subsequent child dying would be less than one in 500, based upon the data.…”
Section: Discussionmentioning
confidence: 91%
“…Eighteen families in the scheme had a second death attributed to SIDS, which gave a relative risk of 5.9 as compared with the population. This study is the largest to date and comes nearest to meeting our criteria, but the accuracy of diagnosis has been questioned 2 14…”
Section: Resultsmentioning
confidence: 99%